Relation of migration trend and gender of RMG labour force in Industrial areas in Bangladesh - Patwary, AKM Asaduzzaman (Daengku: Journal of Humanities and Social Sciences Innovation, 2022)
Legitimate labour migration has, no doubt, got much attention in various economies and labour force irrespective of gender tempt for diverse employment. Industrial employment and job concentration in industrial cluster always provoke work driven migration. People relocate their whereabouts based on their secure livelihoods. And, economic centralization and targeted migration thus associate each other with no exception in Bangladesh. In the 5-decade long industrial history, many changes, reforms and challenges were noticed throughout our industrial ecosystem and labour dynamics. Labour force is a critical strength for efficient and low-cost productivity. In this regard, our mixed labour force, skilled, semi and unskilled workforce, has shaped our local industry and positioned as the most competitive regionally and contributed to gain productivity momentum and foreign trade growth. RMG industry, the forefront export-oriented sector of economy, has emerged as the largest employer of local migrated workforce of all contemporary industries in Bangladesh encouraging labour migration in urban area. This industry shares relatively large in GDP and export earning. With unprecedented contribution by RMG to economy, this study attempted to know whether any relationship of migration trend and gender status since this industry is a female dominant industry. The assessment of correlation is justifiably demanded due to women employment intensity since inception. But, this quantitative research-cause and effect study resulted that gender and migration condition and flow have no positive relationship and integration upon applying non-parametric test Chi-square test of significance. Around 252 independent samples from RMG factories in Dhaka and nearby districts where industrial hubs are located. It has obtained the null and rejected alternative hypothesis. These findings may help for national perspective planning and development planning. The drawn outcomes may also enable us national resource planning, mapping and human development index. As well, we can measure labour productivity in RMG industry and plan for future facility as well urban living and economic development.